The perception of waste management of hikers at Bulusaraung mountain area of Bantimurung Bulusaraung National Park - Heldayanti, Alya; Asrianny, Asrianny; Maulany, Risma Illa (Jurnal Penelitian Kehutanan Wallacea, 2024)
Waste management in tourist destinations is a serious problem because of its non-biodegradable nature and the volume of waste produced each year continues to increase along with the increasing number of visitors to the tourist area. The existence of climbing activities in the Bulusaraung Mountains area has an impact on the waste problem that arises due to hikers activities in the area. This study aims to examine the effectiveness of waste management in the Bulusaraung Mountains, Bantimurung-Bulusaraung National Park (South Sulawesi), Indonesia from the perspective of hikers, a survey was conducted on 100 hikers with a focus on their perceptions, attitudes and awareness using a set of questionnaires. Additionally, observations were made regarding the implementation of hiking procedures applied by the National Park on waste management in the area. A correlation analysis determined the relationship between socio-demographic factors and hikers' perspectives on waste management in the Bulusaraung Mountains. The results, which underscore the importance of this study, indicated that hikers held positive perceptions, attitudes, and awareness regarding the waste management efforts implemented by Bantimurung Bulusaraung National Park. Age and education positively influenced hikersperception, attitude, and awareness towards waste management. In addition, a significant correlation was found between age and awareness (p = 0.05).  Other variables, such as gender, occupation, and organization, were negative and insignificant in influencing hikers' perception, attitude, and awareness (p > 0.05). Respondents‘ education is positively correlated with hikers’ perceptions, attitudes and awareness towards waste management in the Bulusaraung Mountains.